Legal Position and Rights to Sue Community Citizens in Onrechtmatige Overheidsdaad Disputes, Post the Entrance of Law No 30 of 2014 Concerning Government Administration - Andriana, Desmilia Eka; Fadli, Moh.; Negara, Tunggul Anshari Setia; Permadi, Iwan (MultiTech Publisher, 2023)
UU no. 30 of 2014 concerning Government Administration explicitly states that it is possible for Government Officials to be tested by the PTUN. This is of course in order to create good government. This research is normative juridical legal research. This research will analyze the legal position and right to sue the community regarding the Onrechtmatige Overheidsdaad dispute. The research results concluded three things; First, the public has sufficient requirements to file a lawsuit because the legal position and right to sue are regulated in the Decree of the Chief Justice of the Supreme Court Number 36/KMA/SK/II/2013, Law Number 5 of 1986 concerning Administrative Justice, and others. Second, UUAP No. 30 2014 also explicitly states that the government is prohibited from abusing its authority and the PTUN has the authority to decide whether there are elements of abuse of authority. This means that Law Number 30 of 2014 provides space for the public to file a lawsuit. The three definitions of 'Community Citizens' in UUAP No. 30 2014 must be changed after the publication of PERMA Number 01 of 2023 concerning Guidelines for Adjudicating Environmental Cases.